Concept of Islamic Education Perspective of Sayyid Muhammad Naquib Al-Attas - Ahadiah Hanum (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Sayyid Naquib Al-Attas is a figure of reform in Islamic education, he is considered to be the originator of the Islamization of science and has influenced many other figures. He formulated a strategy in forming an educational curriculum for Muslims. Having the full name Muhammad Naquib ibn Ali ibn Abdullah ibn Muhsin Al-Attas, he is a descendant of Rasulullah SAW from Sayyidina Husein whose title is Sayyid. The concept of Islamic education explained by Al-Attas, he offered one term among the three which according to him more accurately refers to the meaning of education, namely Ta'dib. In Arabic the term ta'dib means civilized or adab. According to al-Attas, adab is one of the missions of Rasulullah SAW. So education as something that is no less important in the world will be more focused if conceptualized using the term Ta'dib. Sayyid Naquib Al-attas stated that the aim of Islamic education is not only to produce good citizens and a generation capable of working well, but also to become perfect beings or human beings. The values that need to be prioritized in the goals of education are the values of being a complete human being as a citizen and as an individual who has a spiritual attitude. So it is not human value as a physical manifestation that is pragmatic in its usefulness for the state and society.